No association between tuberculin skin test and atopy in a bacillus Calmette-Guerin vaccinated birth cohort - AKKOÇ, TUNÇ (WILEY, 2009)
Previously, an inverse association was suggested between mycobacterial infection and atopy. We aimed to determine the association between tuberculin skin test (TST) and allergic manifestations in a birth cohort where all infants were vaccinated with bacillus Calmette-Guerin (BCG) at birth. Newborns were enrolled randomly and prospectively followed up for a period of 5 yr. Information on family history and environmental factors was obtained at birth, International Study of Asthma and Allergies in Childhood asthma questionnaire, physical examination, skin prick test to common inhalant and food allergens and TST were performed at 2 and 5 yr of age. Positive TST reactivity was defined as an induration of >= 10 mm. A total of 399 newborns were enrolled, 293 and 125 were available for a followup visit at 2 and 5 yr of age respectively. The prevalence of ever asthma, rhinitis and allergen sensitization tended to increase while eczema decreased with time. No significant association was found between TST reactivity and ever and current wheeze, doctor diagnosed asthma or atopic sensitization both at 2 and 5 yr of age. This prospectively designed birth cohort study did not confirm the previously suggested inverse correlation between TST reactivity and atopic sensitization or any allergic manifestations in Turkish children vaccinated with BCG at birth.
Keywords: allergy; asthma; birth cohort; Mycobacterium tuberculosis; tuberculin skin test; DELAYED-TYPE HYPERSENSITIVITY; EARLY BCG VACCINATION; PERTUSSIS VACCINATION; INVERSE ASSOCIATION; PRESCHOOL-CHILDREN; ALLERGIC DISEASE; ASTHMA; MYCOBACTERIA; INFECTION; RESPONSES